The Time to Assign Ownership in Forward Sale Sontract of Construction - Sahraee, Mohamad; Kaviar, Hosein (Journal of History Culture and Art Research, 2017)
There has been a long-standing controversy between the authors writing for the law regarding the validity of signing a purchase contract concerning the under-construction buildings. All of the law systems have come to this general agreement that the objective of signing a sale contract is the seller’s transfer of ownership to the buyer. Nevertheless, the law authors have been found having disagreements regarding the time and the quality that the ownership should be conveyed. The ratification of the forward sale contract of construction law in 2010 almost put an end to such disputes and the forward sale of the buildings under construction was considered as legally correct and seamless. Although there are yet these questions remaining that “when the ownership should be transferred in such transactions? Should the ownership transfer be taking place with formally establishing and signing a forward sale contract of construction and/or via the final title deed transfer after the building has been completely constructed?” The answers provided by the jurists to these two questions differ in many respects, some of whom know the ownership transfer as the direct and immediate effect of sale and some others, besides sale contract, necessitate other law actions to be taken in order for the ownership transfer to be fully actualized. Forward sale contract of a building is not a newly emergent contract and besides the general rules authenticate for the various types of contracts such agreements follow the specific ordains made in that code of law. In the current research paper, with an applied objective in mind, we are seeking to take advantage of a descriptive-analytical method and also we deal with the explication of the aspects and the limits of the law-related issues and the obligations that have to be shouldered by the forward seller and forward buyer and the exact time that the ownership should be transferred in the extant body of the law rules and regulations on apartment building’s forward sale and the civil law and rules of procedure and registration of our country. Additionally, we are going to make transparent the ambiguous and controversial issue of the time for transferring ownership; thereby, try to clarify the extant ambiguities which have been allegedly found to be the basic contributing factor leading to the emergence of a great deal of bottlenecks and lawsuits for the parties of the forward sale contracts. The findings of the current study are expected to provide us with an efficient leap in sublimating the awareness in the parties interested in law-related field of study.